Equilibrium Adsorption of Two-Component Organic Solutes from Aqueous Solutions on Activated Carbon - A. Seidel; G. Reschke; S. Friedrich; D. Gelbin (Adsorption Science & Technology)
The adsorption equilibria of the mixtures phenol-indol, indol- p -nitrophenol ( p NP), α-picoline-phenol from aqueous solution on activated carbon, mainly Hydraffin 71 and BHT 023/82 have been studied. Significant displacement of one solute by the other was observed. The designation of the more strongly adsorbed component depends on the relative concentration of the two solutes in the mixture and on the pH. Predictive equations for calculating mixture equilibria solely on the basis of single solute isotherms do not agree well with the experimental values; the introduction of empirical parameters determined by curve-fitting is necessary. A multi-Redlich-Peterson equation is derived, which yields a satisfactory representation of most of the present binary solute adsorption data.